Hubungan Paparan Kebisingan, Suhu Ruangan dan Kelembaban Udara Dengan Kualitas Tidur Pasien Di Ruang Intensive Care Unit (ICU) RSUD Banyumas - Istanti, Ervin; Fatwati Fitriana, Nurul (Nursing Sciences Journal, 2024)
Background: Rest and sleep needs must be met for critically ill patients in the ICU. Sleep is necessary for restoring physical function, energy, and immune system building. However, not all critically ill patients in the ICU  have good sleep quality, as several environmental factors can affect sleep quality, including physical environmental hazards such as noise exposure, room temperature, and air humidity, which can risk disturbing patient comfort and safety. Purpose: To determine the relationship between exposure to noise, room temperature and humidity with sleep quality of patients in the intensive care unit (ICU) of Banyumas Hospital. Method: This study is quantitative research with an analytical observational design using a cross-sectional approach. The study population consisted of 20 patients undergoing treatment in the ICU, selected using a random sampling technique. The analysis used in this study is the Spearman rank test. Results: A relationship between noise exposure and sleep quality is indicated by a p-value of 0.010 (p < 0.05) with a correlation coefficient of 0.560. A relationship between room temperature and sleep quality is indicated by a p-value of 0.036 (p <0.05) with a coefficient of 0.471. A relationship between air humidity and sleep quality is indicated by a p-value of 0.010 (p <0.05) with a correlation coefficient of 0.560. Conclusion: There is a relationship between noise exposure, room temperature, and air humidity with patient sleep quality in the Intensive Care Unit (ICU) of Banyumas Regional General Hospital. Keywords: Air humidity, Sleep quality, Noise exposure, Room temperature.